2020
DOI: 10.1186/s12891-020-03509-6
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of individual 3D-printed navigation template for the deep external fixator pin position on the iliac crest

Abstract: Background: The aim of this study was to investigate the feasibility of an individual navigation template for the deep pin position on the iliac crest, based on digital design and 3D printing technology. Methods: The preoperative CT images of 8 patients with pelvic fractures were collected. The data were reconstructed using a 3D imaging reconstruction workstation. An individual navigation template for the deep pin position on the iliac crest was designed on a virtual 3D model. The individual drill template and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Although there was no statistical difference observed in the postoperative hospital stay between the 3D printing group and the conventional group (7.7 ± 4.0 days vs. 7.9 ± 3.8 days). Furthermore, these advantages have also been demonstrated in other bone fractures, particularly in complex fractures around the joints, such as pelvic fractures [ 25 ], pilon fractures [ 26 ], and elbow joint fractures [ 27 ]. With the aid of 3D printing models, one can gain a comprehensive understanding of the three-dimensional structure between fracture fragments, clarify the classification of fractures, and ascertain the relationships among the various fracture fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no statistical difference observed in the postoperative hospital stay between the 3D printing group and the conventional group (7.7 ± 4.0 days vs. 7.9 ± 3.8 days). Furthermore, these advantages have also been demonstrated in other bone fractures, particularly in complex fractures around the joints, such as pelvic fractures [ 25 ], pilon fractures [ 26 ], and elbow joint fractures [ 27 ]. With the aid of 3D printing models, one can gain a comprehensive understanding of the three-dimensional structure between fracture fragments, clarify the classification of fractures, and ascertain the relationships among the various fracture fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative CT images showed that the screws did not penetrate the pedicle cortex, and the average deviation from the expected screw trajectory at the coronal midpoint of the pedicle was 0.87 ± 0.34 mm, indicating that the screw placement was very successful. Liang et al [53] analyzed the practicality of navigation templates in guiding accurate placement of iliac screws. The researchers collected preoperative CT images of eight patients with pelvic fractures to reconstruct a 3D pelvic model, and designed and printed a surgical navigation template for the position of the iliac screw based on this model.…”
Section: Guide Plate For Nail Placementmentioning
confidence: 99%
“…This system allows for the three main VSP steps, i.e., construction of patient-specific geometrical models, virtual bone fracture reduction and virtual bone fracture fixation. The used implant for virtual fixation is often designed using Materialise 3-matic (Materialise, Leuven, Hu et al, 2011;Liu et al, 2013Yang et al, 2013;El-Gengehi and Seif, 2015;Huang et al, 2015, Huang et al, 2020Li et al, 2015Zhang et al, 2015, Zhang et al, 2021Wang et al, 2016a, Wang et al, 2020b, Wang et al, 2020aZeng et al, 2016;Merema et al, 2017;Castro-Núñez et al, 2018;Dreizin et al, 2018;Maini et al, 2018;Sinha et al, 2018;Hung et al, 2019;Marschall et al, 2019;Mishra et al, 2019;Liang et al, 2020;Ramanathan et al, 2020;Agarwal et al, 2021;IJpma et al, 2021;Nasr et Other (self-designed / combination of open-source software) Fornaro et al, 2010a;Vetter et al, 2018;Oki et al, 2021 Total (n = 3): Radius fractures (n = 1), Acetabular/pelvic fractures (n = 1), Fibula fractures (n = 1)…”
Section: Existing Software Solutionsmentioning
confidence: 99%